Lingual and fusiform gyri in visual processing: a clinico-pathologic study of superior altitudinal hemianopia. Issue 5 (May 1987) - Bogousslavsky, J; Miklossy, J; Deruaz, J P; Assal, G; Regli, F
Abstract : A macular-sparing superior altitudinal hemianopia with no visuo-psychic disturbance, except impaired visual learning, was associated with bilateral ischaemic necrosis of the lingual gyrus and only partial involvement of the fusiform gyrus on the left side. It is suggested that bilateral destruction of the lingual gyrus alone is not sufficient to affect complex visual processing. The fusiform gyrus probably has a critical role in colour integration, visuo-spatial processing, facial recognition and corresponding visual imagery. Involvement of the occipitotemporal projection system deep to the lingual gyri probably explained visual memory dysfunction, by a visuo-limbic disconnection. Impaired verbal memory may have been due to posterior involvement of the parahippocampal gyrus and underlying white matter, which may have disconnected the intact speech areas from the left medial temporal structures.